2023
DOI: 10.1097/md.0000000000032625
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of MAD2L1 mediated by ncRNA axis is associated with poor prognosis and tumor immune infiltration in hepatocellular carcinoma: A review

Abstract: Background: The mortality rate and prognosis of patients with hepatocellular carcinoma (HCC) are well known. A variety of highly malignant human cancers express mitotic arrest deficient 2 like 1 (MAD2L1), a transcription factor that plays a critical role in their development and progression. However, MAD2L1’s particular mechanisms and effects on HCC remain uncertain. Methods: We performed a pan-cancer analysis for MAD2L1 prognosis and expression using The Cancer Genome Atla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Few studies have shown that CyclinB1 (CCNB1) is a key gene in the development of liver cancer [34]. Studies have shown that ncRNA-mediated upregulation of MAD2L1 is a predictor of adverse outcomes and tumor invasion in HCC [35]. MiR-200c-5p could inhibit the expression of the MAD2L1 gene, which led to inhibiting the migration, invasion, and proliferation of HCC cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have shown that CyclinB1 (CCNB1) is a key gene in the development of liver cancer [34]. Studies have shown that ncRNA-mediated upregulation of MAD2L1 is a predictor of adverse outcomes and tumor invasion in HCC [35]. MiR-200c-5p could inhibit the expression of the MAD2L1 gene, which led to inhibiting the migration, invasion, and proliferation of HCC cells [36].…”
Section: Discussionmentioning
confidence: 99%